2023
DOI: 10.5194/acp-23-1579-2023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the ice nucleation properties of the kaolin minerals kaolinite and halloysite

Abstract: Abstract. Heterogeneous ice nucleation on dust particles in the atmosphere is a key mechanism for ice formation in clouds. However, the conditions of a particle surface for efficient ice nucleation are poorly understood. In this study, we present results of immersion freezing experiments using differential scanning calorimetry on emulsified mineral dust suspensions, involving the two chemically identical, but morphologically different, kaolin minerals of kaolinite and halloysite. Kaolinite occurs in a platy mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 130 publications
3
9
0
Order By: Relevance
“…Immersion freezing experiments with single particles revealed that not all kaolinite particles are IN active and that the fraction of IN inactive particles increases with decreasing particle size, in accordance with the assumption that ice nucleation is restricted to rare nucleation sites (Lüönd et al, 2010;Welti et al, 2012;Wex et al, 2014;Nagare et al, 2016). Interestingly, kaolinite and halloysite showed an increased IN activity in the presence of ammonia or ammonium solutes (Kumar et al, 2019b;Klumpp et al, 2023), pointing to a similar chemical makeup of nucleation sites as feldspars.…”
Section: Major Subgroups Of Clay Minerals Include Kandite (T-o Layers...supporting
confidence: 64%
See 2 more Smart Citations
“…Immersion freezing experiments with single particles revealed that not all kaolinite particles are IN active and that the fraction of IN inactive particles increases with decreasing particle size, in accordance with the assumption that ice nucleation is restricted to rare nucleation sites (Lüönd et al, 2010;Welti et al, 2012;Wex et al, 2014;Nagare et al, 2016). Interestingly, kaolinite and halloysite showed an increased IN activity in the presence of ammonia or ammonium solutes (Kumar et al, 2019b;Klumpp et al, 2023), pointing to a similar chemical makeup of nucleation sites as feldspars.…”
Section: Major Subgroups Of Clay Minerals Include Kandite (T-o Layers...supporting
confidence: 64%
“…Illite NX and SE consist of 86 wt % and 77 wt % illite, respectively, with kaolinite as the major impurity (10 wt %) and only traces of feldspars and quartz. Moreover, the kaolin mineral halloysite exhibited IN activity up to 245 K in emulsion freezing experiments for samples without quartz or feldspar impurities (Klumpp et al, 2023). Thus, the special peaks of SAu-1 and MX-80 are within the freezing range observed for clay minerals in emulsion freezing experiments, and an origin from smectite INPs is likely.…”
Section: In Activity Of the Smectite Samplesmentioning
confidence: 75%
See 1 more Smart Citation
“…22 Clay aluminosilicate minerals have also been extensively studied both theoretically [24][25][26][27][28] and experimentally. [29][30][31][32][33][34][35] Kaolinite is a common clay mineral and has a unique arrangement of a layer of alumina tetrahedra with hydroxyl groups and a layer of silica tetrahedra with bound oxygen groups. 36 The alumina basal plane is more ice active than the silica basal plane, and in fact, Soni and Patey showed in computational studies that removing the Si layer does not change the ice nucleation activity of the kaolinite by the alumina layer.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, less attention has been given to the pressure dependence of j het , which will be the focus of this study. Negative pressure in water is prevalent throughout nature, occurring in tree xylem (Jacobsen et al, 2007), in water capillary bridges in soil (Seiphoori et al, 2020), and within nano-sized pores on atmospheric ice nucleating particles (David et al, 2020;Marcolli, 2020;Klumpp et al, 2023). Negative Laplace pressure, given by ∆P ≈ σ lv /2r, where σ lv ≈ 0.7 J m −2 is the liquid-vapor surface tension of water, becomes significant for nucleation when the air-water interface radius of curvature r is on the order of nanometers, leading to negative pressures of order 100s of atmospheres.…”
mentioning
confidence: 99%